Response of Boreal Plant Communities and Forest Floor Carbon Fluxes to Experimental Nutrient Additions - Standen, Katherine M.; Sniderhan, Anastasia E.; Sonnentag, Oliver; Voigt, Carolina; Baltzer, Jennifer L. (Ecosystems (New York), 2024)
High-latitude warming is increasing soil temperatures and driving permafrost thaw, potentially altering soil nutrient conditions by enhancing microbial mineralization and making nutrients from previously frozen soils accessible for plant and microbial use. Increases in soil nutrient concentrations may alter plant community processes and, consequently, carbon (C) fluxes. We conducted an experiment in a boreal permafrost peatland, monitoring forest floor C flux and functional traits of the entire moss and vascular plant communities to the addition of nutrients at 20 and 40 cm soil depths and under closed and open canopy conditions. Plant functional trait responses were investigated at both community level (using community-weighted means) and intraspecific scales. Using fertilizer additions, we emulated nutrient increases at different depths in the soil profile, replicated at high and low canopy cover sites to assess the influence of light availability. Our results demonstrate rapid responses of vascular plant community-level traits as well as ecosystem respiration and gross primary productivity to fertilization treatments under low canopy cover, suggesting an influence of local environmental variation. We found that moss community-level traits played a more important role in mediating C flux response to nutrient fertilization than vascular plants but led to little change in C sink–source dynamics. This provides insight into existing ambiguities of the response of boreal C fluxes to increased nutrient availability following soil warming and permafrost thaw: Local environmental conditions and moss community can strongly mediate the response, whereas vascular plant communities may play a more minor role. However, our results suggest that these changes may not alter overall C sink–source dynamics of peatlands in the near term.